Operando X-ray absorption spectroscopy study of the Fischer-Tropsch reaction with a Co catalyst - Nayak, Chandrani; Jain, Preeti; Vinod, C. P.; Jha, S. N.; Bhattacharyya, D. (Journal of Synchrotron Radiation, 2019)
This article describes the setting up of a facility on the energy-scanning EXAFS beamline (BL-09) at RRCAT, Indore, India, for operando studies of structure-activity correlation during a catalytic reaction. The setup was tested by operando X-ray absorption spectroscopy (XAS) studies performed on a Co-based catalyst during the Fischer-Tropsch reaction to obtain information regarding structural changes in the catalyst during the reaction. Simultaneous gas chromatography (GC) measurements during the reaction facilitate monitoring of the product gases, which in turn gives information regarding the activity of the catalyst. The combination of XAS and GC techniques was used to correlate the structural changes with the activity of the catalyst at different reaction temperatures. The oxide catalyst was reduced to the metallic phase by heating at 400 degrees C for 5h under H-2 at ambient pressure and subsequently the catalytic reaction was studied at four different temperatures of 240, 260, 280 and 320 degrees C. The catalyst was studied for 10h at 320 degrees C and an attempt has been made to understand the process of its deactivation from the XANES and EXAFS results.
Keywords: catalysis; EXAFS; Fischer-Tropsch reaction; in situ studies; structure-activity correlation; XANES

Shape-controlled MoO3/MnO x nanocatalyst for the selective synthesis of 2-phenylquinoxaline drug motifs - Singh, Nittan; Putla, Suresh Babu; Pratap Singh, Chandrodai; Kalbande, Pavan Narayan; Choudhary, Priyanka; Krishnamurty, Sailaja; Krishnan, Venkata; Bhatte, Kushal; Sudarsanam, Putla (ACS Applied Nano Materials, 2023)
We have developed a highly effective shape-controlled MoO3/MnOx nanocatalyst for the selective synthesis of 2-phenylquinoxaline drug motifs at room temperature without any external oxidant. Electron microscopy images reveal that the MnOx material contains rod-shaped particles (length: 500-1000 nm and width: 150-200 nm) and the MoO3 species are uniformly dispersed in the MoO3/MnOx material. The MoO3/MnOx nanocatalyst calcined at 500 degrees C (MoO3/MnOx-5) contains abundant strong acid sites and an optimum ratio of Mn4+/Mn3+, which are responsible for the C-N cross-coupling reaction between 2-phenylethylamine and o-phenylenediamine, giving higher yields (>96%) of 2-phenylquinoxaline at mild conditions. The broad scope of this catalytic strategy at room temperature and without an external oxidant was confirmed by achieving >90% yields of functional 2-phenylquinoxalines from C-N cross-coupling of various o-phenylenediamines and 2-phenylethylamines. The outstanding reusability efficiency of the MoO3/MnOx-5 nanocatalyst up to five cycles without the need for a regeneration step as well as the effective scalability highlighted the practicability of the MoO3/MnOx-based catalytic protocol for carbon-heteroatom coupling reactions at room temperature and without an external oxidant. Using computational studies, the possible reasons for the selective synthesis of 2-phenylquinoxaline over the MoO3/MnOx-5 nanocatalyst were elucidated.
Keywords: cascade C-N cross-coupling; DFT studies; room temperature andopen air; shape-controlled MoO3/MnOx nanocatalyst; structure-activity correlation